Utilizing a Rapid Prototyping Approach in the Building of a Hypermedia-Based Reference Station - Sell, Dan. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This paper discusses the building of a hypermedia-based reference station at the Wright Laboratory Technical Library, Wright-Patterson Air Force Base, Ohio. Following this, the paper focuses on an electronic user survey from which data is collected and analysis is made. The survey data is used in a rapid prototyping approach, which is defined as system development based on continuous user input. The prototype reference station (in reality hypertext at present and not yet hypermedia), named "AskMe," was introduced in April 1994, and the study was conducted by an on-line survey instrument available on AskMe. Overall, the low number of responses, only nine over two months, was disappointing. Survey results were not a good evaluation of AskMe's effectiveness, but this does not mean that the method is useless. At this point in the rapid prototyping process, the best way to evaluate AskMe is through communication among the developer, other library staff, and users. The rapid prototyping approach appears to lie outside the paradigm of conventional research because it appendix includes the survey instrument. (Contains 35 references.) (SLD/MAS)
ERIC Note: Master's Research Paper, Kent State University.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Computer Software Development; Hypermedia; Information Dissemination; Information Systems; Library Services; Models; Online Systems; Reference Services; Research Methodology; Surveys; Systems Development; Users (Information); Prototypes; Wright Patterson Air Force Base; Dissertations/Theses.; Tests/Questionnaires.